Corporate Governance and Firm Performance of Listed Small and Medium-Sized Enterprises in China - Huang, Yiyi (2022)
The purpose of this dissertation is to explore the relationship between corporate governance and firm performance of small and medium-sized firms in China. Based on data analysis from a sample of 517 listed small and medium-sized firms over a five-year period (2016-2020), this dissertation suggests that corporate governance has a considerable impact on the performance of listed small and medium-sized enterprises in China. According to the findings of the data analysis, board size, CEO age, CEO compensation, board independence, CEO duality, and insider ownership have a substantial impact on the performance of listed small and medium-sized firms in China, whereas CEO tenure does not appear to be a significant determinant of firm performance. This dissertation advances our understanding of the relationship between corporate governance and firm performance and has significant consequences for business executives, policymakers, and academics who prescribe corporate governance for small and medium-sized enterprises.